THE ROLE OF THE AGENT ENVIRONMENT IN SOCIETY (Modern education and development, 2025)
This article examines the role and importance of agent environments in society. Agent-based systems, with their autonomous and interactive features, are widely used in various areas of society. The article describes in detail how agents are used in modeling social systems, analyzing economic processes, predicting epidemics in healthcare, urban planning, and many other areas, and how they affect society.